25 Biological failure following acl reconstruction. (13th October 2015) - Akhtar, MA; Keating, JF
Abstract : Biological ACL graft failure is a complex pathological entity. This results in an atonic, disorganised and non-viable graft. Our aim was to study biological failure in patients undergoing revision ACL reconstruction. We studied 72 patients undergoing revision ACL reconstruction between 1996 and 2010. These patients were divided into redundant ACL (Group A–36 patients) if the graft was in continuity but lax and non-functional and ruptured ACL (Group B–36 patients) if the graft was not in continuity at the time of revision surgery. The mean age and gender difference were similar in both groups. The duration of time from primary ACL reconstruction to failure was 41 months in group A and 38 months in group B (p = 0.69). The graft used for primary ACL reconstruction in group A was quadruple hamstring tendon in 55%, patella tendon in 24%, double hamstring in 7% and allograft in 7%. The cause of failure in group A was classified as traumatic in 43%, technical error in 3%, trauma and technical error in 11% and biological failure in 43%. The mean Beighton score was 4.2(0–9). The graft used for primary ACL reconstruction in group B was quadruple hamstring tendon in 53%, patella tendon in 25%, double hamstring in 13% and synthetic graft in 10%. The cause of failure was classified as traumatic in 58%, technical error in 11%, trauma and technical error in 3%, infection in 6% and biological failure in 22%. The mean Beighton score for group B was 1.8 (0–4). The biological failure was higher in the redundant ACL group 43% vs 22% (p = 0.04). The mean Beighton score was higher in redundant ACL Group 4.2 vs 1.8 but this difference was not statistically significant (P = 0.07). Our findings suggest that biological failure was higher in the redundant ACL grafts and it should be suspected in patients without a history of trauma or technical error. Further research is needed to assess if generalised ligamentous laxity is a risk factor for biological failure after ACL reconstruction.